Impact evaluation of the extreme weather event in mangroves of the Brazilian Southeast Coast with remote sensing - Silva, Marco Antonio Saraiva; Faria, André Luiz Lopes (Sociedade & Natureza, 2022)
Among the various environments present on the planet that deserve due attention, as they have particularities and specificities of chemical, physical and biological orders, mangroves stand out. These ecosystems are mostly located in the intertropical zones where continental and oceanic waters meet, being crucial for a great diversity of animal species that find, in it, conditions that allow them to live and reproduce. In addition, this ecosystem is also for many local residents, such as traditional fishermen and crab farmers, a place for income generation, thus assuming an important socio-economic function. In addition, mangroves, through vegetation, help to protect the coast and act as important carbon sequestrants and stores. Among the less invasive methodologies that make it possible to analyze a series of dynamics of this environment, reducing costs with the field and the risks inherent to its natural characteristics, Remote Sensing stands out. Therefore, the general objective of this research was to evaluate the effectiveness of the NDVI, SAVI and LAI vegetation indices in recording the consequences of an extreme climatic event that occurred on June 1, 2016, in the mangroves of the Reserva de Desenvolvimento Sustentável Municipal Piraquê Açu-Mirim, located in Aracruz (ES), Southeast Coast Brazil. To achieve the objective, time series between February 2016 (before the event) and December 2020 were used. The results, which include maps and statistical graphs, allowed the delimitation of areas according to the intensities of the impacts and their consequences on the vegetation. While the vegetation of Piraquê-Açu underwent regeneration processes in all affected areas, in Piraquê-Mirim the area with the greatest impact remained destroyed. Given the socio-environmental importance of mangroves, it is necessary to implement projects aimed at their recovery. Both the methodology and the indices were efficient to achieve the objectives and can be reproduced in other mangroves.